Energy expenditure related to routines of different aerobic Gymnastics awards - Cheung, A. Y.; Fung, L. (International Journal of Fitness, 2008)
The aim of this study was to identify the energy requirements of completing the Aerobic Gymnastics Bronze, Silver, or Gold Badges Scheme offered by the Gymnastics Association of Hong Kong, China. 128 participants (17 males and 111 females) took part in this study and the age-range of participants was from 6 to 16 years old. They were divided into three age groups (aged 8 years and below = 35, aged 9-11 years= 64, aged 12 years and above = 29). They performed the routine according to the award level (Gold =8, Silver =5, Bronze =115). The BioTrainer Pro and the Polar Heart-rate monitor were used to assess energy requirement and record heart-rate response over the exercise period respectively. Participants were asked to wear the BioTrainer Pro and the Polar Heart-rate monitor, and performed the Bronze/Silver/ Gold routine three times with a 30 seconds rest interval. The exercise heart rate and total energy expenditure for males and females were similar. The eldest group has the highest energy expenditure, F (2, 88) = 6.45, p = .002. (aged12 & above: 6.45 + 2.2 kcal.min-1; aged 9-11: 4.34 + 2.2 kcal.min-1; aged 8 & below: 4.55 + 2.5 kcal.min-1). The total energy expenditure for the gold award level was significantly higher than the bronze level, F(2, 88) = 7.02, p =.001. (Gold: 7.46 + 1.4 kcal.min-1; Silver: 6.75 + 2.6 kcal.min-1; Bronze: 4.56 +2.3 kcal.min-1). The Caloric Expenditure for aerobic gymnastics for the trial 1, 2, 3 was 0.156 cal.min-1kg-1; 0.153 cal.min-1kg-1; and 0.154 cal.min-1kg-1 respectively. Thus, aerobic gymnastics meets the intensity level that warrants it to be classified as an appropriate activity for developing cardiovascular fitness and/or weight loss.